(untitled) (Research, Society and Development, 2021)
Among all Cannabinoids, Cannabidiol (CBD) proved to be significantly anti-inflammatory in a multiplicity of pathological conditions and with the lack of drugs and effective and 100% safe prophylaxis, inducing the scientific community to carry out several clinical trials, where they were done tests of the anti-inflammatory profile of the CBD associated with Lung Inflammation (Cytokine Storm) caused by the virus and similar conditions. Consequently, Covid-19 induces significant damage to humans through the storm of pro-inflammatory cytokines. A bibliographic search was made on Lung Inflammation related to viral inflammatory mediators and an alternative therapy, one found the use of Cannabidiol in clinical trials. It is important to note that Cannabidiol has several anti-inflammatory properties, which may represent a potential adjunctive therapeutic anti-inflammatory substance against inflammation induced by Covid-19 in defensive cells.